Representation of Organizational Culture and Communication: An Ethnographic Study on Intergenerational Women’s Leadership in a Nursing Home - Nela Rizqilillah; Deddy Mulyana; Yanti Setianti (ETNOSIA : Jurnal Etnografi Indonesia, 2026)
Organizational culture in social service institutions is not merely a static administrative framework but a living system of shared meanings constructed through daily interactions. While studies on nursing homes have documented various institutional frameworks, research that specifically examines organizational culture through the intersection of intergenerational women's leadership and cultural transmission within a historically rooted, female-exclusive nursing home remains scarce. This study addresses this gap by exploring how intergenerational women’s leadership shapes the representation of organizational culture and communication practices at Panti Sosial Tresna Wredha Budi Pertiwi, an institution that has maintained a unique intergenerational women's leadership model since 1947. Specifically, this study aims to analyze this representation through Edgar Schein’s three levels of culture: artifacts, espoused values, and basic underlying assumptions. Using a qualitative approach with an ethnography of communication lens, data were gathered through in-depth interviews, field observations, and documentary studies. Data were analyzed using a qualitative flow model, structured around Edgar Schein’s three-level framework of culture. The findings reveal that the institution's resilience is sustained through four interconnected dimensions. First, intergenerational women's leadership serves as the historical and relational foundation of the institution, positioning leaders as guardians of tradition rather than mere administrators. Second, this leadership fosters a distinct organizational culture built upon shared values of gotong royong, sincerity, and respect for the elderly's dignity. Third, this culture is enacted through communication practices that are highly dialogical, egalitarian, and rooted in collective decision-making, creating a family-like atmosphere among administrators, staff, and residents. Fourth, these dynamics are systematically manifested through Schein's three levels of culture: spiritual artifacts that build sisterhood, the aforementioned espoused values, and the basic underlying assumption that caregiving is an act of sacred devotion. Consequently, the integration of these four dimensions allows the nursing home to preserve its historical identity across generations.